Fabrication of textile fabric counter electrodes using activated charcoal doped multi walled carbon nanotube hybrids for dye sensitized solar cells. Issue 4 (12th January 2016) - Arbab, Alvira Ayoub; Sun, Kyung Chul; Sahito, Iftikhar Ali; Memon, Anam Ali; Choi, Yun Seon; Jeong, Sung Hoon
Abstract : Textile fabric electrodes have attained increasing demand as they offer the benefits of light weight, flexibility, and low cost. Abstract : Textile fabric electrodes have attained increasing demand as they offer the benefits of light weight, flexibility, and low cost. In this work, we fabricated an activated charcoal doped multi walled carbon nanotube (AC doped MWCNT) hybrid and printed on polyester woven fabric. This carbon fabric composite was used as a counter electrode (CE) in dye sensitized solar cells (DSSCs), so as to replace expensive platinized FTO (fluorinated tin oxide) glass. A variety of mesoporous carbon structures were synthesized by using different types of charcoal together with MWCNTs. Morphological characterization revealed that the highly porous defect rich carbon structure consists of synchronized features of 3D carbon decorated with the MWCNT network. The excessive oxygen surface groups can reduce a large amount of polymer gel electrolyte and locate manifold catalytic sites for the reduction of tri-iodide (I3 − ). Electrochemical investigations confirmed that this carbon fabric composite has high electrocatalytic activity (ECA) and exhibited a very low charge transfer resistance ( R CT ) of 1.38 Ω. The resulting N719 DSSCs consisting of this unique carbon coated textile fabric CE filled with the polymeric electrolyte show a power conversion efficiency (PCE) of 7.29%, outperforming the platinized FTO glass CE. Such facile assembly of this novel textile fabric CE is quite promising for the mass production of next generation textile structured solar cells.